Evaluation of the treatment results in patients with rhegmatogenous retinal detachment treated by pars plana vitrectomy with air: Preliminary results. Issue 22 (June 2018) - Michalska-Małecka, Katarzyna; Sierocka-Stępień, Justyna; Michalik-Jakubek, Aneta; Witek, Katarzyna; Nowomiejska, Katarzyna; Jünemann, Anselm; Rejdak, Robert
Abstract: Purpose: The aim of this study was to evaluate the effectiveness of treatment and the restoration of the anatomic conditions (retinal reattachment) in rhegmatogenous retinal detachment treated by pars plana vitrectomy (PPV) using air as endotamponade. Methods: Twelve patients (12 eyes) with rhegmatogenous retinal detachment were included in the study. These were eyes with retinal detachment both with and without macular involvement. During the PPV surgery, the peripheral and central part of the vitreous body was excised to eliminate the formation of vitreoretinal traction after surgery, laser therapy was performed peripherally and in retinal openings, and the eyeball was filled with filtered air. Local conditions were evaluated at 1, 7, 14, 30, 90, and 180 days after the procedure. Results: The result of the patients' examination on the 30 th day after surgery showed that 100% of cases achieved retinal reattachment and improved vision (best corrected visual acuity). In the long-term assessment, the final visual acuity was better in 11 patients (91.7%) compared to the initial results. On average, 7 days after the surgery, air in the eyeball occupied about one-fifth of the vitreous chamber and was completely absorbed about 10 to 14 days after surgery. Conclusions: In the above-mentioned study, very good results of treatment of open-rooted retinal detachment were achieved. The air was quickly absorbed and visual acuity improved. Owing to the relatively fast absorption time, this method could be used successfully in high altitude patients and people often travelling by airplane. Abstract : Supplemental Digital Content is available in the text